Analisis Pelaksanaan Kemitraan Dengan Kunjungan Ibu Balita Ke Posyandu Tahun 2016 - Hidayat, Hilda (Lembaga Layanan Pendidikan Tinggi (LLDIKTI) Wilayah X, 2018)
Health promotion is very important in anticipating the behavior to mobilize mothers to Posyandu. Health promotion give partnership, technical rule, human resources, money, method and facility help the mother to visit posyandu. Nanggalo Health Center which has a rate visit new mothers to Posyandu is 43.2% and highest 77.1% in Lubuk Buaya Health Center with a target of 80%. The research has done in January until Juny 2016 was conducted using qualitative research in two Health Centre. The qualitative data was collected using interview guideline to 6 informants, document analysis and observation. Qualitative data processing by triangulation. At two health center there is no technical rule, financial resources, and Region Budget Income and Health Operational Financial. At Nanggalo Health Centre, Health Promotion Officer as posyandu officer, and then at Lubuk Buaya Health Centre Health Promotion Officer as activity coordinator. Lubuk Buaya Posyandu stay at citizen home and facilities are available but in Nanggalo hasn’t. Partnership Lubuk Buaya Health Centre run as expected compare Nanggalo Health Centre cause of that the mother to visit posyandu almost reach of target. Health Centre make technical rule to hold posyandu training, and health promotion manual direction. Promosi Kesehatan sangat penting meningkatkan kunjungan ibu balita ke posyandu. Tujuan promkes mengetahui pelaksanaan kemitraan, petunjuk teknis, SDM, dana, metode, saranadengan tingkat kunjungan ibu balita ke posyandu. Di Puskesmas Nanggalo kunjungan ibu balita terendah (43,2%) dan tertinggi (77,1%) Puskesmas Lubuk Buaya dari target 80%. Penelitian dilaksanakan Januari sampai Juni 2016 dengan metode kualitatif di kedua puskesmas. Pengumpulan data dengan wawancara mendalam (6 informan), telaah dokumen dan observasi. Pengolahan data dengan triangulasi. Di kedua puskesmas belum ada petunjuk teknis, sumber dana APBD dan BOK. Di Puskesmas Nanggalo, petugas promkes pelaksana posyandu, sedangkan di Puskesmas Lubuk Buaya petugas promkes pengkoordinir kegiatan. Posyandu Lubuk Buaya menetap di rumah warga dan sarana sudah tersedia, sedangkan di Nanggalo belum ada. Kemitraan Puskesmas Lubuk Buaya berjalan baik dibandingkan Puskesmas Nanggalo. Puskesmas membuat petunjuk teknis, mengadakan pelatihan posyandu, dan buku pedoman.